A brief approach oriented to the creation of shared value from the university: The Institute of Social Economy and Cooperativism (Indesco), Universidad Cooperativa de Colombia - Monroy Flores, Verel Elvira; Pérez Muñoz, Colombia (DIXI, 2020)
Purpose: By way of reflection, the aim of this paper is to approach how to create shared value from the Institute of Social Economy and Cooperativism (Indesco), which translates into concrete actions, developed in several of the eighteen campuses that make up the Cooperative University of Colombia.Description: In these brief lines, an exercise of extrapolation of the work of Indesco is made based on the theoretical proposal of “shared value” submitted by the authors Michael E. Porter and Mark R. Kramer.Methodology: the methodology used is documentary research, since an exercise was carried out to review video recordings, newsletters, minutes, decrees, among others.Viewpoint: Given its history, the Institute of Social Economy and Cooperativism (Indesco), in order to complement its work of social innovation, must strive to build territories of solidarity that leverage the economic, social and human development of the Colombian regions; this is a particular way of creating shared value.Conclusions: It is hoped that this exercise of reflection will serve as a provocation to the institutions of the cooperative and solidarity sector to evaluate and make visible, in their own way, how they create shared value. Likewise, higher education institutions should extrapolate their experiences to make a collective construction of what it means to create shared value with a university perspective.
Keywords: good practices; higher education; solidarity-based economy; supportive territory; cooperativism